Insights into the bioactive compounds, antioxidant potential and TLC profiling of different extracts of Tomato plants (Jahangirnagar University Journal of Biological Sciences, 2018)
Tomato (Solanum lycopersicum L.) is a widely cultivated vegetable crop worldwide and its consumption is increasing day by day. The only edible part of tomato plant is its fruit. Therefore, the residual tomato plant parts are considered as waste after fruit collection despite some portion of it is used as livestock feed and in the production of fertilizer. Moreover, due to the consumption issue, much of the research is focused on tomato fruit rather than other plant parts. Bioactive compounds can be present in any part of the plant and can be isolated and recovered. Therefore, tomato plant may be useful as a source of bioactive compounds. Our study focuses on the phytochemical constituents and bioactive compounds that are present in different parts of the tomato plant that were being less studied before. Qualitative phytochemical tests were performed to identify the presence of different bioactive compounds. Saponins, tannins, glycosides, phenols, alkaloids, flavonoids and resins are present in significant amount. Total phenol, total flavonoids, total tannin, and total protein content were measured quantitatively. Leaf samples showed higher concentrations of bioactive compounds than roots and stem. Highest total phenol content (66.43 mg/g), total flavonoids content (28.00 mg/g), total tannin content (7.36 mg/g) and total protein content (26.55 mg/g) was found from the leaf water extract. DPPH scavenging assay was performed to find the antioxidant potential and positive results were found. Thin layer chromatography (TLC) was also employed to check the constituents. Our study found several spots for different samples and their retention factors (Rf) were evaluated.Jahangirnagar University J. Biol. Sci. 7(2): 65-77, 2018 (December)